Semantic Analysis of Hypernym and Hyponym in The“Twilight Saga: Breaking Dawn Part 2” - Adek Halim Arrasyid; Hilma Safitri; Kayla Azira Ratnapuri; Mayzia Sabiha Fidhinillah; Sulistiani (INDO PUBLISHING, 2025)
The objective of this observation is to explore the connection between Hyponymy as a semantic feature and the movie entitled Twilight Saga: Breaking Dawn Part 2. As a part of Semantics, a hyponym is a particular word that represents a general term, referred to as a hypernym. The study employed a descriptive qualitative approach, which involved analyzing the movie transcript to categorize words as hypernyms and hyponyms. Data had been gathered primarily based on the association with hyponyms concerning semantics analysis. The hyponyms are discovered in a total of 40 hyponyms in this observation. There are nine general terms: (1). 18 names, (2). 4 clans, (3). 1 ethnic, (4). 5 families, (5). 1 country, (6). 4 cities, (7). 1 animal, (8). 4 parts of the body, (9). 3 supernatural creatures.